2018
DOI: 10.1002/mawe.201700264
|View full text |Cite
|
Sign up to set email alerts
|

The modified temperature term on Johnson Cook model for AZ31 magnesium alloy

Abstract: The quasi‐state and dynamic mechanism of AZ31 magnesium alloy at a strain rates range of 0.001 s‐1–2500 s‐1 under a temperature range of 20 °C–250 °C were researched by compression tests using the electronic universal testing machine and split Hopkinson pressure bar system. The true stress‐strain curves at different strain rates and evaluated temperatures were obtained. The result shows that the thermal soften effect of AZ31 magnesium alloy is significant. By modifying the temperature term of the original John… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…To ensure the accuracy of the experiment and test data obtained, the compression testing was repeated three times. The detailed experimental procedure can be found elsewhere [24].…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…To ensure the accuracy of the experiment and test data obtained, the compression testing was repeated three times. The detailed experimental procedure can be found elsewhere [24].…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Mao et al [12] studied the dynamic compressive mechanical properties and failure behaviour of extruded Mg–8Gd–5Y magnesium alloy with an average grain size of about 10 µm, which belongs to the same category of alloy system as Mg–7Gd–5Y–1.2Nd–0.5Zr. The results of high strain rate compression showed that the extruded magnesium Mg–8Gd–5Y alloy specimens yielded continuously along ED, TD, and ND directions, and exhibited a positive strain rate effect; however, their anisotropy was not as obvious as that of commercial magnesium alloy AZ31 [13].…”
Section: Introductionmentioning
confidence: 99%